Penerapan Konseling Individu dengan Teknik Latihan Asertif dalam Mereduksi Perilaku Insecure pada Remaja - Diah Nur Azizah; Zhila Jannati; Bela Janare Putra (Journal of Society Counseling, 2025)
This study aims to describe the application of individual counseling using assertive training techniques to reduce insecure behavior in adolescents at TPQ Amaliah Palembang. The method used was qualitative with a case study approach. Data were collected through direct observation, semi-structured interviews with five informants (students, parents, and TPQ administrators), and documentation. The results show that individual counseling with assertive training techniques is effective in reducing insecure behavior among adolescents, as evidenced by increased self-confidence following a staged counseling process involving role-playing, modeling, and positive reinforcement. Students who initially showed symptoms such as fear of speaking in public, avoidance of social situations, and excessive self-comparison gradually became more expressive, braver in sharing their opinions, and more confident in participating in class activities. Supporting factors include the positive therapeutic relationship between counselor and student, peer support, and consistent praise, while time limitations and the complexity of individual psychological problems were identified as obstacles. This study concludes that assertive training as part of individual counseling is an effective approach to address insecure behavior in adolescents.